Impact and behavior of Sn during the Ni/GeSn solid‐state reaction. Issue 3 (14th April 2020) - Quintero, Andrea; Gergaud, Patrice; Hartmann, Jean-Michel; Delaye, Vincent; Reboud, Vincent; Cassan, Eric; Rodriguez, Philippe
Abstract : A comprehensive analysis focused on Sn segregation during the Ni/GeSn solid‐state reaction was carried out. It was demonstrated that Sn is soluble in the various Ni/GeSn intermetallic phases and that, when the temperature increases, the Sn segregation occurs first at grain boundaries, which can hamper Ni diffusion and delay the intermetallic formation. Abstract : Ni‐based intermetallics are promising materials for forming efficient contacts in GeSn‐based Si photonic devices. However, the role that Sn might have during the Ni/GeSn solid‐state reaction (SSR) is not fully understood. A comprehensive analysis focused on Sn segregation during the Ni/GeSn SSR was carried out. In situ X‐ray diffraction and cross‐section transmission electron microscopy measurements coupled with energy‐dispersive X‐ray spectrometry and electron energy‐loss spectroscopy atomic mappings were performed to follow the phase sequence, Sn distribution and segregation. The results showed that, during the SSR, Sn was incorporated into the intermetallic phases. Sn segregation happened first around the grain boundaries (GBs) and then towards the surface. Sn accumulation around GBs hampered atom diffusion, delaying the growth of the Ni(GeSn) phase. Higher thermal budgets will thus be mandatory for formation of contacts in high‐Sn‐content photonic devices, which could be detrimental for thermal stability.